Influence of reaction parameters on the fate of nitrogen during the supercritical water gasification of dewatered sewage sludge. (September 2022) - Gong, Miao; Wang, Linlu; Hu, Jinxiang; Feng, Aixin; Wang, Mengqi; Fan, Yujie
Graphical abstract: Highlights: Effects of reaction parameters on N fate during SCWG of DSS were investigated. N distribution and morphology were most affected by temperature and then time. The solid phase contained more inorganic-N and less protein-N after SCWG. The proportion of N-containing compounds in biocrude was between 0.26% and 20.34%. The major proportion of N was transformed into liquid then solid and biocrude. Abstract: This study investigated the effects of different parameters on the fate of nitrogen (N) in products after supercritical water gasification (SCWG) of dewatered sewage sludge (DSS). N distribution and morphology were most affected by temperature, followed by reaction time and heating rate, while reaction pressure had little effect on them. In terms of specific performance, higher temperature, longer reaction time, and slower heating rate were beneficial to the increase of NH4 + -N content in the liquid phase. Compared with raw sludge, after SCWG, the solid phase contained more inorganic-N and less protein-N, a certain proportion of quaternary-N and nitrile-N. The proportion of N-containing compounds in the biocrude phase was between 0.26%–20.34%, suggesting the importance of more research on N in the biocrude phase. The recovery rate of N in all samples was between 64.34%–93.82%. The major proportion of N (42.27%–60.91%) was transformed into the liquid phase, while the remaining entered the solid phase (10.54%–21.45%) and the biocrude phase (6.18%–15.78%). These findings are helpful to better understand the principle of N distribution in products of DSS after SCWG and provide some new ideas for reducing N-containing by-product formation in the future.